Using adaptive equalizing in LTE with MIMO - Al-Janabi, Hussam Dheaa (Eastern-European Journal of Enterprise Technologies, 2012)
The given work is devoted to the analysis of using method of equalization in LTE systems with different MIMO configuration for purpose increasing characteristics quality of communication. Although equalizers promise to improve the signal to noise energy ratio, zero forcing (ZF) equalizers are derived classically in a deterministic setting minimizing intersymbol interference, while minimum mean square error (MMSE) equalizer solutions are derived in a stochastic context based on quadratic Wiener cost functions. The problem of InterSymbol Interference (ISI) and the basic concept of transversal equalizers are introduced followed by a simplified description of some practical adaptive equalizer structures and their properties. Adaptive equalizers compensate for signal distortion attributed to intersymbol interference, which is caused by multipath within time-dispersive channels